THE RIGHT TO REPAIR OF DAMAGES IN THE EVENT OF AFFECTION OF THE INDIVIDUAL FREEDOM OF THE PERSON DURING THE CRIMINAL PROCEEDINGS - LORINCZ, Anca-Lelia (International Journal of Legal and Social Order, 2022)
Starting from the need to respect, in any judicial procedure, the right to liberty and security of the person, in order to guarantee public safety and ensure a high level of social capital, this study addresses the issue of reparation for damage to the individual's liberty during the criminal proceedings. The paper presents the special procedure for reparation of material damage or non-pecuniary damage in case of illegal deprivation of liberty in the regulation of the current Romanian Code of Criminal Procedure, with the interpretations given by the High Court of Cassation and Justice for ensuring a unitary judicial practice, as well as with the aspect of unconstitutionality ascertained by the Decision of the Constitutional Court of Romania no. 136/2021. In the context of the legislative interventions envisaged by the latest draft law on amending and supplementing the Code of Criminal Procedure, concrete regulatory proposals are made in the paper so that this special procedure guarantees the exercise of the right to reparation for all situations of unlawful or unjust deprivation of liberty in the course of criminal proceedings, according to the standard of protection established by the European Convention for the Protection of Human Rights and Fundamental Freedoms. The possibility of extending the scope of the special reparation procedure to the case of impairment of individual liberty by restrictive measures of liberty is also being considered.